Mapping Poverty in Afghanistan : Technical Report - World Bank Group (World Bank, Washington, DC, 2019)
Afghanistan has been in protracted conflict for almost four decades, with direct implications on progress towards development objectives. This context of recurring episodes of violence and insecurity, economic and political instability, and the consequent displacement of populations within and outside the nation’s borders has important implications on the landscape of data and evidence available for the design, implementation, monitoring and evaluation of interventions and programs, and their timeliness and relevance. Afghans represent the world’s largest and most protracted refugee population, with an estimated 3.5 million people currently living abroad as refugees for more than four decades. Given the large disparities in poverty incidence and high levels of inequality within Afghanistan, the knowledge of living standards at more disaggregated geographical levels of districts and nahias could help inform policy design and improve decision making at a sub-province level. Therefore, poverty mapping, which aims at estimating poverty incidence at levels lower than the household survey, was applied in Kabul and Herat provinces. This technical report describes the methodology and data used to produce the Kabul and Herat poverty maps and presents the resulting collection of poverty maps, the first of its kind for Afghanistan. The structure of the report is as follows. Section 2 outlines the poverty mapping methodology, specifically the small area estimation approach, applied in Afghanistan. Section 3 discusses the data sources and the various technical challenges faced with the datasets. Section 4 discusses the modeling phase, including model selection, model parameters, and assumptions. Section 5 presents the poverty maps at a district and nahia level, and section 6 concludes. The Annexes contains supporting data and analysis.